2017
DOI: 10.1371/journal.pone.0178689
|View full text |Cite
|
Sign up to set email alerts
|

The effect of alcohol on the differential expression of cluster of differentiation 14 gene, associated pathways, and genetic network

Abstract: Alcohol consumption affects human health in part by compromising the immune system. In this study, we examined the expression of the Cd14 (cluster of differentiation 14) gene, which is involved in the immune system through a proinflammatory cascade. Expression was evaluated in BXD mice treated with saline or acute 1.8 g/kg i.p. ethanol (12.5% v/v). Hippocampal gene expression data were generated to examine differential expression and to perform systems genetics analyses. The Cd14 gene expression showed signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 58 publications
1
4
0
Order By: Relevance
“…With these information, we analyzed the effect of alcohol on TGFβR1 and showed that alcohol induces TGFβR1 expression in lung fibroblasts and mouse lung while alcohol did not affect TGFβR2 expression in our experimental model (data not shown). This data is similar to the work published by Zhou et al showing that alcohol upregulated TGFβR1 expression in mouse hippocampus [28]. However, the mechanism by which alcohol regulates TGFβR1 is to be elucidated.…”
Section: Discussionsupporting
confidence: 92%
“…With these information, we analyzed the effect of alcohol on TGFβR1 and showed that alcohol induces TGFβR1 expression in lung fibroblasts and mouse lung while alcohol did not affect TGFβR2 expression in our experimental model (data not shown). This data is similar to the work published by Zhou et al showing that alcohol upregulated TGFβR1 expression in mouse hippocampus [28]. However, the mechanism by which alcohol regulates TGFβR1 is to be elucidated.…”
Section: Discussionsupporting
confidence: 92%
“…In contrast, haloperidol‐induced gene expression was related to inflammatory and immune pathways, with the transcriptional regulation of ion channels being a common effect of chronic clozapine and haloperidol treatment . The analysis of the network of ethanol‐responsive genes related to proinflammatory cytokine cascade indicated novel interactions between alcohol and the immune system . Finally, a substantial impact on the alterations in expression profile induced by psychotropic drugs was observed for the network of genes related to circadian rhythm (eg, Per1 , Per2 and Bmal1 ) …”
Section: Drug‐regulated Gene Expression Networkmentioning
confidence: 99%
“…PI3K-AKT plays an important role in the formation and development of depression (Gong et al, 2021). The MAPK pathway is the key pathway of in ammatory cytokine production and can regulate the expression of in ammatory genes at post-transcription level (Zhou et al, 2017). Some studies have shown that neuronal apoptosis plays an important role in the development of depression (Shen et al, 2018).…”
Section: Molecular Docking Resultsmentioning
confidence: 99%